2020
DOI: 10.1111/jfpe.13457
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on collision acceleration and damage characteristics of potato

Abstract: To reveal the mechanism of potato mechanical damage, this article investigated the relationships between the collision characteristics of potato and various impact parameters using potato impact test rig and acceleration acquisition system. It was noted that the potato impact test rig and acceleration acquisition system allowed simultaneously analysis of the three indexes: maximum acceleration, minimum acceleration, and damaged area. In the experiments, the collision damaged area of potato increased with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…And the frictional force increased when the contact area increased, which leaded to the larger MFCA. Both Xie [7] and Geyer [9] placed the acceleration sensors inside potatoes to test the normal collision acceleration. Results found that the larger the potato mass was, the smaller the maximum acceleration would be.…”
Section: Effect Of Potato Mass and Rod Direction On Mfcamentioning
confidence: 99%
See 4 more Smart Citations
“…And the frictional force increased when the contact area increased, which leaded to the larger MFCA. Both Xie [7] and Geyer [9] placed the acceleration sensors inside potatoes to test the normal collision acceleration. Results found that the larger the potato mass was, the smaller the maximum acceleration would be.…”
Section: Effect Of Potato Mass and Rod Direction On Mfcamentioning
confidence: 99%
“…Researchers had also found similar results when analyzing the characteristics of the maximum acceleration for potatoes and rods in the normal collision. [7,10]…”
Section: Effect Of Initial Height On Mfcamentioning
confidence: 99%
See 3 more Smart Citations